Government Procurement: Processes, Challenges, and Perspectives of Implementers - Crisostomo, Ace Angelo; Dura, Alger (International Journal of Sustainability and Advanced Integrated Research, 2026)
Government procurement is essential to effective public service delivery but remains challenged by complex procedures, extensive documentary requirements, and operational inefficiencies. This study explored the lived experiences of procurement implementers in the City Government of Tagum to examine government procurement processes, implementation challenges, strategies, and insights for improving procurement performance. The study was anchored on the Stages Model of Public Policy and New Public Management Theory. A qualitative phenomenological research design was employed, involving 20 purposively selected procurement implementers. Data were collected using a validated researcher-developed interview guide through in-depth interviews and analyzed using thematic analysis following Colaizzi's phenomenological approach. The findings revealed that procurement implementation is characterized by procurement planning, documentary verification, procurement mode selection, digitalization, and accountability mechanisms. Major challenges included documentary inefficiencies, budget and resource constraints, workflow bottlenecks, and workforce limitations. Procurement implementers addressed these challenges through stakeholder capacity-building, monitoring and tracking mechanisms, inter-office coordination, proactive planning, legal compliance, and quality assurance. The study concludes that strengthening digital procurement systems, continuous capacity-building, stakeholder collaboration, and procurement process improvement can enhance procurement efficiency, transparency, accountability, and public service delivery. It recommends continued procurement modernization, expanded training programs, strengthened supplier engagement, enhanced inter-office collaboration, and further studies on the implementation of Republic Act No. 12009. The study mainly aligns with Sustainable Development Goal (SDG) 12: Responsible Consumption and Production by supporting sustainable public procurement practices. Its findings contribute to institutional, governance, and socio-economic sustainability by providing evidence that may strengthen procurement implementation, improve public resource management, and support responsive local governance.
Keywords: Philippine Government Procurement; Local Government Units; Phenomenology; Procurement Implementers; Procurement Planning; Public Procurement; Qualitative Research; RA 9184; RA 12009